Perancangan Website E-Commerce Deal! Dalam Jual-Beli Barang Bekas - Pane, Khairil Sa’bansyah; Ritonga, Rizal Amri Khoirul Hakim; Daulay, Muhammad Mushab Umair; Gunawan, Nasrullah; Maharani, Nur Zahra (CV. ITTC INDONESIA, 2024)
In this digital era, e-commerce websites are growing very rapidly. Technological advances have a major impact on economic growth including businesses around the world, including Indonesia. E-commerce is one of the advanced technologies that greatly encourages the progress of digital business in Indonesia. Technological advances not only present new opportunities but also change the way people interact in business activities. E-commerce, as a form of technological innovation, plays an important role in supporting the growth of the digital economy by providing convenience in buying and selling transactions without space and time limits. Therefore, designing an optimal e-commerce website is a strategic step to meet the needs of the growing market. This study aims to design an e-commerce website that is not only functional and responsive, but also user-friendly, by paying attention to aesthetic aspects, ease of navigation, and security in transactions. With this approach, the designed website is expected to be able to provide a comfortable, safe, and satisfying online shopping experience, as well as contribute to increasing business competitiveness in the digital era.